Life cycle greenhouse gas evaluation of organic rankine cycle using refuse-derived fuel from municipal solid waste - Netchanakan Sununta (2018)
© 2017 Author(s). In Thailand, the rise in population and economic growth have caused waste generation to increase rapidly, leading to increases in greenhouse gases (GHGs) being released to the atmosphere from waste landfills. Application of waste-to-energy technology to produce electricity can reduce waste accumulation in landfills in addition to lessening the GHG emissions. This study aimed to evaluate life cycle GHG emissions from application of organic Rankine cycle (ORC) as waste-to-energy technology using refuse-derived fuel (RDF), which is produced from municipal solid waste, according to the life cycle assessment approach. The functional unit is defined as 1 kWh. The results indicate that the GHG emissions of 1 kWh of power generated from a RDF hybrid with an ORC power generation system are mostly contributed from RDF combustion in the operation stage, which accounts for 77% of the total. The RDF hybrid ORC shows fewer GHG emissions than the existing combustion-based power generation in Thailand, except for natural gas with the combined-cycle technology. The RDF hybrid ORC power generation can reduce 51.47% of GHG emissions when compared with an open dump, and 34.31% when compared with a landfill. The RDF hybrid ORC was also demonstrated as an environmentally friendly system that can be considered as a source of power generation in power planning in the future.